2011
DOI: 10.1002/app.34106
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a chiral stationary phase with poly[styrene‐b‐cellulose 2,3‐bis(3,5‐dimethylphenylcarbamate)] by surface‐initiated atom transfer radical polymerization and its chiral resolution efficiency

Abstract: A chiral stationary phase (CSP) with poly[-styrene-b-cellulose 2,3-bis(3,5-dimethylphenylcarbamate)] was synthesized by the surface-initiated atom transfer radical polymerization (SI-ATRP) of cellulose 2,3-bis(3,5-dimethylphenylcarbamate)-6-acrylate after the SI-ATRP of styrene on the surface of silicon dioxide supports in pyridine. The successful preparation of the CSP with poly[styrene-b-cellulose 2,3-bis(3,5-dimethylphenylcarbamate)] was confirmed via Fourier transform infrared spectroscopy, field emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Hydrophilic monomers with potential use in biomedical applications include N -acryloylmorpholine (NAM), , 4-hydroxyphenylethyl methacrylate (HPEMA), , N -( p -vinylbenzyl)-phthalimide (VBP) and a dendronized form of PEGMA . Monomers with pendant carbohydrate residues such as 2-(2,3,4,6-tetra-O-acetyl-β- d -glucosyloxy)­ethyl methacrylate (AcGEMA), glucosylureaethyl methacrylate (GUMA), 4-vinylbenzenesulfonamidoethyl 1-thio-β-D-saccharides (VBSAEZ), N -2–4-(vinylbenzenesulfonamido)­ethyl lactobionamide (VBSAELA), , 2′-acrylamidoethyl D-pyranosides (AAEP), glucosamine-derivatized GMA and cellulose derivatives , offer novel platforms for biosensors and chiral stationary phases due to specific interactions with biomolecules, such as proteins.…”
Section: Synthetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrophilic monomers with potential use in biomedical applications include N -acryloylmorpholine (NAM), , 4-hydroxyphenylethyl methacrylate (HPEMA), , N -( p -vinylbenzyl)-phthalimide (VBP) and a dendronized form of PEGMA . Monomers with pendant carbohydrate residues such as 2-(2,3,4,6-tetra-O-acetyl-β- d -glucosyloxy)­ethyl methacrylate (AcGEMA), glucosylureaethyl methacrylate (GUMA), 4-vinylbenzenesulfonamidoethyl 1-thio-β-D-saccharides (VBSAEZ), N -2–4-(vinylbenzenesulfonamido)­ethyl lactobionamide (VBSAELA), , 2′-acrylamidoethyl D-pyranosides (AAEP), glucosamine-derivatized GMA and cellulose derivatives , offer novel platforms for biosensors and chiral stationary phases due to specific interactions with biomolecules, such as proteins.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…Choi and co-workers prepared chiral stationary phases by SI-ATRP of vinylated cellulose 2,3-bis­(3,5-dimethylphenylcarbamate). These polymer brushes were grown either directly from silica or from silica grafted with an initial polystyrene block . The authors demonstrated enantiomer separation of stilbene oxide, benzoin, 2-phenylcyclohexanone, cobalt­(III) trisacetylacetonate, d , l -sec-phenylethyl alcohol, Tröger’s base, 2,2,2-trifluoro-1-(9-anthryl)­ethanol and flavanonein.…”
Section: Properties and Novel Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most popular routes, SI-ATRP is a convenient and useful method for synthesizing polymers with well-controlled molecular weights and distributions. 35,36…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most popular routes, SI-ATRP is a convenient and useful method for synthesizing polymers with well-controlled molecular weights and distributions. 35,36 Generally speaking, macrocyclic glycopeptides have the disadvantage of large steric hindrance for CSP synthesis as chiral selectors. Thus, Zhang et al 37 prepared a vancomycinbonded CSP by the immobilization of vancomycin onto amino-containing silica using glutaraldehyde as a spacer arm.…”
Section: Enantioseparation Of Chiral Drugs In Hplcmentioning
confidence: 99%